Digital Technology and the Practices of Humanities Research - Edmond, Jennifer (Open Book Publishers, 2020)
"How does technology impact research practices in the humanities? How does digitisation shape scholarly identity? How do we negotiate trust in the digital realm? What is scholarship, what forms can it take, and how does it acquire authority? This diverse set of essays demonstrate the importance of asking such questions, bringing together established and emerging scholars from a variety of disciplines, at a time when data is increasingly being incorporated as an input and output in humanities sources and publications. Major themes addressed include the changing nature of scholarly publishing in a digital age, the different kinds of 'gate-keepers' for scholarship, and the difficulties of effectively assessing the impact of digital resources. The essays bring theoretical and practical perspectives into conversation, offering readers not only comprehensive examinations of past and present discourse on digital scholarship, but tightly-focused case studies. This timely volume illuminates the different forces underlying the shifting practices in humanities research today, with especial focus on how humanists take ownership of, and are empowered by, technology in unexpected ways. Digital Technology and the Practices of Humanities Research is essential reading for scholars, students, and general readers interested in the changing culture of research practices in the humanities, and in the future of the digital humanities on the whole."